Plato’s Socrates and the Law Code of Athens - Jinek, Jakub (My University, 2021)
The paper claims that Socrates’ disawoval of wisdom in the Apology is not to be taken too seriously since it belongs to the rhetorical strategy of the sovereign philosopher who speaks in front of the crowd. In the political arena, the philosopher admits his obligation to become a philosopher-king, but only under a condition: only if his fellow-citizens would freely recognize his legitimacy to rule. As a potential ruler, he has to take into consideration the existing law code which is to be respected if his intended political reform should take place and succeed. The paper stresses that despite Plato’s condemnation of the democratic way of life current in Athens, he never criticizes Athenian laws; Solonian legal reform forms a starting point for his own political project. As a brief glance at the proposed law code of Magnesia in Plato’s Laws makes clear, the Platonic philosopher is full of respect to the Athenian legislative tradition.
Platónův Sókratés a athénský zákoník
Keywords: Plato’s Socrates; philosopher-king; Solon; Law Code of Ancient Athens; Athenian democracy